2015
DOI: 10.9738/intsurg-d-13-00142.1
|View full text |Cite
|
Sign up to set email alerts
|

Fecoflowmetric Analysis of Anorectal Motor Function in Postoperative Anal-Preserving Surgery Patients With Low Rectal Cancer Comparison With the Wexner Score and Anorectal Manometry

Abstract: The aim of this study was to elucidate whether fecoflowmetry (FFM) could evaluate more detailed evacuative function than anorectal manometry by comparing between FFM or anorectal manometric findings and the clinical questionnaires and the types of surgical procedure in the patients who received anal-preserving surgery. Fifty-three patients who underwent anal-preserving surgery for low rectal cancer were enrolled. The relationships between FFM or the manometric findings and the clinical questionnaires and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…FFM has been reported to be an accurate and useful tool for assessing postoperative anorectal motor function [19]. It was introduced by Shafik and Abdel-Moneim [20] as a dynamic method for examining the anorectal motor activity that could simulate the natural act of defecation.…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…FFM has been reported to be an accurate and useful tool for assessing postoperative anorectal motor function [19]. It was introduced by Shafik and Abdel-Moneim [20] as a dynamic method for examining the anorectal motor activity that could simulate the natural act of defecation.…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%
“…The evacuative rate was then calculated [ER = (EV/TV) × 100(%)]. Ryu et al [19] reported that compared to the Wexner score and manometry, FFM was relatively useful for providing a quantitative and comprehensive postoperative evaluation of the anorectal motor function in patients who had undergone a SPS.…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%
“…The defecated volume, flow time, mean and maximum flow rates, and time to maximum flow rate are obtained by simulating diarrhea to calculate the defecation flow curve [59]. The efficacy of fecoflowmetry for evaluating postoperative anorectal motility is equivalent to that of the symptom severity score and anorectal manometry [60]. Endoscopic ultrasonography can detect lacerations of the sphincter and changes in the puborectal angle in patients with LARS.…”
Section: Assessment and Testing Of Larsmentioning
confidence: 99%
“…299 FI was diagnosed with one technique in 142 (46.4%) studies (questionnaires in 141 studies 51,54,56,5860,62–64,6671,74,79,81,84,8789,93,94,97,99102,108,112,116121,124, 126,128132,135140,143145,147,149,150,154,156,158–161,166,169,177, 181,182,…”
Section: Resultsmentioning
confidence: 99%